THE EFFECT OF DASH DIET EDUCATION USING THE PEER GROUP METHOD ON THE EATING PATTERNS OF DIABETES MELLITUS PATIENTS IN KALIBUNTU VILLAGE - Wicaksono, Kurniawan Erman; Rahmat, Nafolion Nur; Purwanza, Sena Wahyu; Nurmawati, Ida; Hanifa, Salihati (Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2025)
The management of diabetes mellitus (DM) includes diet management as an important component in maintaining blood sugar stability. The DASH diet helps maintain electrolyte balance and cardiovascular health through calcium, potassium, and magnesium intake. Dietary education using the peer group method is useful for sharing experiences, exchanging information, and providing and receiving emotional support.. This study aimed to determine the effect of DASH diet education using the peer group method on the eating patterns of Diabetes Mellitus (DM) patients. The research design was pre- experimental with a one-group pretest-posttest approach. The study population consisted of 40 respondents, with a total sampling technique, and the data were analyzed using the Wilcoxon Sign Rank Test. After receiving DASH diet education, most patients had good eating patterns. The study results showed that DASH diet education using the peer group method had an effect on the eating patterns of Diabetes Mellitus patients. Based on the study findings, it was expected that community nurses could use DASH diet education interventions to improve blood sugar levels, lipid profiles, and blood pressure in diabetes mellitus patients.